Utilization of Microalgae in Aquaculture System: Biological Wastewater Treatment - Kyochan Kim; Joo-Young Jung; Hyon-Sob Han (Ital Publication, 2019)
We recently developed an autotrophic biofloc technology (ABFT) system entailing simultaneous microalgae co-culturing with juvenile-farming-stage fish and shrimp in aquaculture and microalgae-based water treatment. The present study was conducted to confirm the potentialities of the ABFT system at the remaining stages (seedling to adult farming, Nile tilapia) for industrial-level implementation. In the results at the seedling stage, an excellent water-purification effect and significant water conservation (97% reduction) by microalgae were verified. Indeed, among the fish, there were not any significant differences, either in growth performance or in body composition, and the wastewater from this system was recycled by use for the growth of various plants. Further, the ABFT system was demonstrated to have a positive effect on production economics by simplifying the production process steps (simultaneous fish breeding and wastewater treatment) and providing for a natural hatching environment. In summary, the ABFT system can be integrated with existing systems on an industrial level as an effective and efficient means of achieving sustainable aquaculture.